Spinal cord ischemia after resection of thoracoabdominal aortic aneurysms: MR findings in 24 patients. - Mawad, M E; Rivera, V; Crawford, S; Ramirez, A; Breitbach, W (American Journal of Neuroradiology, 1990)
MR images of the thoracic spinal cord were made in 24 patients who developed signs and symptoms of spinal cord ischemia or infarction following surgery for a thoracoabdominal aortic aneurysm. Findings consisted primarily of four different patterns of signal abnormalities in the distribution of the anterior spinal artery. These abnormalities were identified as types A-D, depending on the degree of involvement of the gray matter and surrounding white matter. We found good correlation between the distribution of the signal abnormalities in the cord, the severity of the neurologic deficits, and the clinical outcome. MR is the imaging method of choice for diagnosing spinal cord ischemia or infarction. A thorough knowledge of the spinal cord arterial territories is crucial for characterizing ischemic MR signal abnormalities and for differentiating them from other causes of myelopathy.